2016
DOI: 10.1128/aac.01781-15
|View full text |Cite
|
Sign up to set email alerts
|

A Replicative In Vitro Assay for Drug Discovery against Leishmania donovani

Abstract: The protozoan parasite Leishmania donovani is the causative agent of visceral leishmaniasis, a disease potentially fatal if not treated. Current available treatments have major limitations, and new and safer drugs are urgently needed. In recent years, advances in high-throughput screening technologies have enabled the screening of millions of compounds to identify new antileishmanial agents. However, most of the compounds identified in vitro did not translate their activities when tested in in vivo models, hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 30 publications
2
54
0
Order By: Relevance
“…For example, it has been demonstrated that following 72 hours exposure of HEK293 cells to EdU there was cytotoxicity displayed, with an IC 50 value of 0.060 ± 0.043 μM identified [32]. A recent report has described lack of toxicity of EdU toward L. donovani following 72 hours incubation [20]. It could be that these parasites have different methods of transport / variability in enzymes for nucleoside analogue incorporation into their DNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been demonstrated that following 72 hours exposure of HEK293 cells to EdU there was cytotoxicity displayed, with an IC 50 value of 0.060 ± 0.043 μM identified [32]. A recent report has described lack of toxicity of EdU toward L. donovani following 72 hours incubation [20]. It could be that these parasites have different methods of transport / variability in enzymes for nucleoside analogue incorporation into their DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Incorporation of EdU into parasite DNA, detected with click chemistry, has recently been used as a chemical probe to identify replicating T. cruzi parasites, to assess variation in strain replication and responses to a selection of compounds at a single concentration [19]. Additionally, an image-based assay to assess parasite replication utilising EdU as a chemical probe was developed to determine compound activity against Leishmania donovani [20]. The incorporation of EdU and BrdU has been compared in T. cruzi epimastigotes and it was found that EdU was most effective for monitoring DNA replication because of its sensitivity and that DNA denaturation is not required [21].…”
mentioning
confidence: 99%
“…Cell lines are often used over primary cells due to ease of culture and an argument of homogeneity. Phorbol 12-myristate 13-acetate (PMA)-differentiated THP-1 cells are widely used in antileishmanial drug research, but different stimulation conditions are reported (7,8,10,22). The host cell's ability to sustain infection with Leishmania parasites and comparison of the potencies of reference compounds to other host cells and assay formats have been the focus in developing protocols for antileishmanial drug evaluation using differentiated THP-1 cells.…”
mentioning
confidence: 99%
“…The InMac assay developed by GSK was modified by the incorporation of horse serum which increased the robustness and the predictive potential of the assay by reducing the amount of extracellular promastigotes remaining after infection 17 . Moreover, it avoided the reinfection and increased the replication rate of intracellular amastigotes 17 . The assay was further optimized for the clinical isolates LdBPK_282 and LdBPK_275 (procedure described in Fig.…”
Section: Resultsmentioning
confidence: 99%